PERBANDINGAN KEKUATAN PENGELASAN LISTRIK DENGAN PENGELASAN GAS PADA MATERIAL BESI SIKU JIS G3101 - Dwi Atmaja Mukti; Rudy Poeng; Tertius V Y Ulaan (JURNAL POROS TEKNIK MESIN UNSRAT, 2015)
The research was to compare two types of welding, i.e. electric welding and gas welding for the strength and the yield stress of a brackets made of angle steel conformÂ  to JIS G 3101 material.TheÂ  results of strength has been done by previous researcher (Tumurang, 2014), while this research doing the strength of gas welding. The research shows that electric welding gives a better effect than gas welding. The tensile stress is 33.865%better, and the yield stress is 48.843% better. It is concluded that the welding of the material JIS G 3101 brackets is more appropriate to use the electrical welding than using gases of welding. Keywords: Strength of welding, Angle steel, Tensile test.